KONFLIK SOSIAL DALAM NOVEL KOBARAN CINTAKU KARYA RATNA SARUMPAET - Alfarissy Vega Husaini Putera (sarasvati, 2019)
This research study analysis in the form of better about social unrest in a novel Kobaran Cintaku. In assessing novel Kobaran Cintaku researchers used qualitative research methods of analyzing the form of descriptive, description not be the number or coefficient about the relationship between variables. The conflict contained in the novel Kobaran Cintaku: the first conflict between fellow individuals. Conflict strife of different opinions. The second conflict between individuals and group of torture and kidnapping. The third the conflict between fellow group in conflict oppression and war.